Circulating Skeletal Troponin During Weaning From Mechanical Ventilation and Their Association to Diaphragmatic Function: A Pilot Study - Spadaro, Savino; Dalla Corte, Francesca; Scaramuzzo, Gaetano; Grasso, Salvatore; Cinnella, Gilda; Rosta, Valentina; Chiavieri, Valentina; Alvisi, Valentina; Di Mussi, Rosa; Volta, Carlo Alberto; Bellini, Tiziana; Trentini, Alessandro (Frontiers in Medicine, 2021)
Background: Patients with acute respiratory failure (ARF) may need mechanical ventilation (MV), which can lead to diaphragmatic dysfunction and muscle wasting, thus making difficult the weaning from the ventilator. Currently, there are no biomarkers specific for respiratory muscle and their function can only be assessed trough ultrasound or other invasive methods. Previously, the fast and slow isoform of the skeletal troponin I (fsTnI and ssTnI respectively) have shown to be specific markers of muscle damage in healthy volunteers. We aimed therefore at describing the trend of skeletal troponin in mixed population of ICU patients undergoing weaning from mechanical ventilation and compared the value of fsTnI and ssTnI with diaphragmatic ultrasound derived parameters. Methods: In this prospective observational study we enrolled consecutive patients recovering from acute hypoxemic respiratory failure (AHRF) within 24 hours from the start of weaning. Every day an arterial blood sample was collected to measure fsTnI, ssTnI and global markers of muscle damage, such as ALT, AST and CPK. Moreover, Thickening fraction (TF) and diaphragmatic displacement (DE) were assessed by diaphragmatic ultrasound. The trend of fsTnI and ssTnI was evaluated during the first 3 days of weaning. Results: We enrolled 62 consecutive patients in the study, with a mean age of 67 ± 13 years and 43 of them (69%) were male. We did not find significant variations in the ssTnI trend (p = 0.623), but fsTnI significantly decreased over time by 30% from Day 1 to Day 2 and by 20% from Day 2 to Day 3, (p < 0.05). There was a significant interaction effect between baseline ssTnI and DE (F(2)=4.396, p = 0.015), with high basal levels of ssTnI being associated to a higher decrease in DE. On the contrary, the levels of fsTnI were characterized by significant higher DE at each time point. Conclusions: Skeletal muscle proteins have a distinctive pattern of variation during weaning from mechanical ventilation. A high basal value of ssTnI were associated to a higher decrease over time of diaphragmatic function while high values of fsTnI were associated to a higher displacement at each time point.